2016
DOI: 10.1161/circresaha.116.308357
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Coronary Endothelial Dysfunction Have Impaired Cholesterol Efflux Capacity and Reduced HDL Particle Concentration

Abstract: Rationale Coronary endothelial dysfunction (ED)–an early marker of atherosclerosis–increases the risk of cardiovascular events. Objective We tested the hypothesis that cholesterol efflux capacity and HDL particle concentration predict coronary ED better than HDL-cholesterol (HDL-C). Methods and Results We studied 80 subjects with non-obstructive (<30% stenosis) coronary artery disease. ED was defined as <50% change in coronary blood flow in response to intra-coronary infusions of acetylcholine during diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…2, 17 This generalization appears to be refuted by results of cholesterol efflux studies on HDL such as the present work by Monette et al , 5 earlier macrophage efflux studies, 4, 18, 19 as well as by numerous findings in preclinical models. 20 Moreover, a recent study identified a rare loss of function variant of SCARB1 , the gene encoding SR-BI.…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…2, 17 This generalization appears to be refuted by results of cholesterol efflux studies on HDL such as the present work by Monette et al , 5 earlier macrophage efflux studies, 4, 18, 19 as well as by numerous findings in preclinical models. 20 Moreover, a recent study identified a rare loss of function variant of SCARB1 , the gene encoding SR-BI.…”
mentioning
confidence: 50%
“…3 Studies in humans have indicated that the macrophage cholesterol efflux capacity of HDL is a strong inverse predictor of subclinical atherosclerosis and CVD, and remains highly statistically significant after correction for HDL-cholesterol levels, 4 suggesting that HDL cholesterol levels may be a poor surrogate for key functions of HDL mediating anti-atherogenic effects. In this issue of Circulation Research , Monette et al 5 measured acetylcholine-induced coronary artery vasodilation, an indicator of endothelial NO bioavailability, in subjects undergoing coronary angiography, and showed that the cholesterol efflux capacity of HDL correlated inversely with coronary endothelial dysfunction (ED), a key event in early atherogenesis. In contrast, HDL and LDL cholesterol levels did not correlate with coronary ED.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a small study, the concentration of medium-sized HDL particles was selectively lower in subjects with advanced carotid atherosclerotic disease, independent of HDL-C levels [21]. Also, altered HDL particle concentration—but not HDL-C levels—predicts endothelial dysfunction as assessed by coronary angiography, supporting the notion that the size and concentration of HDL particles is an independent predictor of CVD risk [50]. …”
Section: Unresolved Issues In Hdl Metabolismmentioning
confidence: 94%